Deltora quest. Volume 2 - Niwano, Makoto, 1964-; Kobayashi, Mayumi; Rodda, Emily (New York : Kodansha Comics, 2011)
Jarred, who once swore to the true king of Deltora that he would retrieve the seven gems of the Belt of Deltora and use the belt's magical power to restore peace to the kingdom, has prepared his son Lief to fulfill his oath. Now sixteen years old, Lief and his comrade Barda, once one of the king's guard, undertake Jarred's quest to wrest the gems and power from the Shadow King.
"A Kodansha Comics trade paperback original"--T.p. verso.
"First published in Japan in 2006 by Kodansha, Ltd., Tokyo"--T.p. verso.
"T Ages 13+"--Cover p. [4].
Translated from the Japanese.
Translation of: Derutora kuesuto.
Adult.
Keywords: Rodda, Emily -- Adaptations; Rodda, Emily -- Adaptations; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Orphans -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Fantasy graphic novels; Friendship -- Comic books, strips, etc -- Fiction; Good and evil -- Comic books, strips, etc -- Fiction; Graphic novels; Inheritance and succession -- Comic books, strips, etc -- Fiction; Magic -- Comic books, strips, etc -- Fiction; Manga; Orphans -- Comic books, strips, etc -- Fiction; Fantasy comic books, strips, etc; Graphic novels